Cerodontha (Poemyza) unisetiorbita Zlobin (Diptera Agromyzidae) new far Europe (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence of Cerodontha (Poemyza) unisetiorbita Zlobin, mining on Phyllostachys mitis A. et C. Riviére, has been recorded. It is believed that the insect has been in Italy for many years, because some specimens have been caughtin different places, very distant from each other. The most important morphological and biological characteristics are given.
Keywords: Cerodontha unisetiorbita, Diptera Agromyzidae, new records, Phyllostachys mitis.; Cerodontha unisetiorbita; Diptera Agromyzidae; new records; Phyllostachys mitis